PERANCANGAN SISTEM INFORMASI LAND TRANSPORTATION ASSISTANCE TAXI PUSKOPAU PADA BANDARA XYZ - Fadel Arif Novianto; Hari Purwanto (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2022)
The Lamd Transportation Assistance System is a familiar thing at XYZÂ  Airport. However, the problem of getting in and out of taxis performing pickups still cannot be solved. Managing land transportation support using a manual system leads to common mistakes. Manual systems that really require accuracy and a very complicated process are still used in the development of the company to enter and report data to and from PUSKOPAU taxis performing pickups. Therefore, the Lamd Transportation Assistance system can solve the data entry problem and provide data reports quickly and accurately. With this research, the authors create a new system using a coded programming language that makes it easier to enter, save, and create Lamd Transportation Assistance data reports. The new system uses the coded programming language. Thus, this study can improve the efficiency and effectiveness in processing data.Â Keywords: System, Land Transportation Assistance, Kodular, Android